Formarea competenţelor: perspectiva enactivă [Articol] - Cabac, Valeriu (USARB, 2020)
This article discusses the possibility of defining the notion of professional competence as a dual approach: as resources and as a resource mobilization process. Arguments are made that not only the human mind but also the whole body participates in the formation of competences.
Keywords: competence; dual definition; resources; complex situations; enaction